KpnI restriction endonuclease and methyltransferase exhibit contrasting mode of sequence recognition - Chandrashekaran, Siddamadappa (Oxford University Press, 2004)
The molecular basis of the interaction of KpnI restriction endonuclease (REase) and the corresponding methyltransferase (MTase) at their cognate recognition sequence is investigated using a range of footprinting techniques. DNase I protection analysis with the REase reveals the protection of a 14–18 bp region encompassing the hexanucleotide recognition sequence. The MTase, in contrast, protects a larger region. KpnI REase contacts two adjacent guanine residues and the single adenine residue in both the strands within the recognition sequence 5′-GGTACC-3′, inferred by dimethylsulfate (DMS) protection, interference and missing nucleotide interference analysis. In contrast, KpnI MTase does not show elaborate base-specific contacts. Ethylation interference analysis also showed the differential interaction of REase and MTase with phosphate groups of three adjacent bases on both strands within the recognition sequence. The single thymine residue within the sequence is hyper- reactive to the permanganate oxidation, consistent with MTase-induced base flipping. The REase on the other hand does not show any major DNA distortion. The results demonstrate that the differences in the molecular interaction pattern of the two proteins at the same recognition sequence reflect the contrasting chemistry of DNA cleavage and methylation catalyzed by these two dissimilar enzymes, working in combination as constituents of a cellular defense strategy.